Fractional spinal anesthesia and systemic hemodynamics in frail elderly hip fracture patients [version 3; peer review: 1 approved, 2 approved with reservations] - Keti Dalla; Sven-Erik Ricksten; Fredrik Olsen; Mathias Hård af Segerstad; Bengt Nellgård (F1000Research, 2023)
Background: Systemic haemodynamic effects of intrathecal anaesthesia in an aging and frail population has not been well investigated. We examined the systemic haemodynamics of fractional spinal anaesthesia following intermittent microdosing of a local anaesthetic and an opioid. Methods: We included 15 patients aged over 65 with significant comorbidities, planned for hip fracture repair. Patients received a spinal catheter and cardiac output monitoring using the LiDCOplus system. All measurements were performed prior to start of surgery. Invasive mean arterial pressure (MAP), cardiac index (CI), systemic vascular resistance index (SVRI), heart rate and stroke volume index (SVI) were registered. Two doses of bupivacaine 2.25 mg and fentanyl 15 µg were administered with 25-minute intervals. Hypotension was defined as a fall in MAP by >30% or a MAP <65 mmHg. Results: The incidence of hypotension was 30%. Hypotensive patients (n=5) were treated with low doses of norepinephrine (0.01-0.12 µg/kg/min). MAP showed a maximum reduction of 17% at 10 minutes following the first dose. CI, systemic vascular resistance index and stroke volume index decreased by 10%, 6%, and 7%, respectively, while heart rate was unchanged over time. After the second dose, none of the systemic haemodynamic variables were affected. Conclusions: Fractional spinal anaesthesia administered prior to surgery induced a minor to moderate fall in MAP, mainly caused by a reduction in cardiac output, induced by systemic venodilation, causing a fall in venous return. Our results are contrary to the widely held belief that hypotension is mainly the result of a reduction of systemic vascular resistance.